169k views
11 votes
6 + 8x - 3 + 2x = 536 Solve for x.

2 Answers

2 votes

Answer:

53.3

Explanation:

first combine like terms 6-3 = 3 and 8x plus 2x = 10 x so our simplified equation is: 10x + 3 = 536

subtract 3 from 536 because we are moving it from the other side

so we have 10x = 533 then divide 533 by 10 to get x by itself.

User Shubham Tyagi
by
5.2k points
0 votes

Answer:

x=533/10 or 53.3

Explanation:

Let me know if you need an explanation :)

User Aravind Reddy
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.